Main control - Miller, John; British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1976)
Discusses about main control in broadcasting
Converted into VHS 1/2 in.
Title from title screen
Film editor, Des Murphy ; film cameraman, Michael Smee
Narration : Michael Smee
Keywords: Broadcasting; Communication